Analisis Perbandingan Laporan Keuangan Komersial dan Laporan Keuangan Fiskal dalam Rangka Menghitung Pajak Penghasilan Terutang (Studi Kasus pada CV. Makmur Jaya Mulia di Bandar Lampung) - Thontowie Dauli; . Maryati; Syamsu Rizal (Jurnal Akuntansi dan Keuangan, 2010)
The purpose of this study was to determine the difference between the financial statement presentation of commercial and fiscal financial statements, identify the posts in the commercial financial statements need to be corrected and adapted according to the applicable tax provisions, as well as understand how the calculation of corporate income tax payable in accordance with the applicable provisions. After studying the financial statements of the company and the estimates slightly its estimate-the elements that affect the amount of taxable income, and compare it with the provisions of the tax laws that apply to the calculation of tax payable on the CV. Jaya Makmur Mulia, then some conclusions can be drawn as follows: 1. Taxation laws embraced self assessment system, which taxpayers are given the trust to calculate and pay tax obligations. Thus the taxpayer is required to have accounting records as a means to count as taxable income. 2. Differences between the financial statements of commercial and financial statements for the fiscal occurs commercial financial statements is calculated based on the applicable accounting standards, while the fiscal financial statements is calculated based on the laws of the Republic Indonesia no. 17 of 2000 on income tax. The difference can be divided into two different temporary and permanent differences (time). In the CV. Jaya Makmur Mulia permanent differences is included in the cost of entertainment, gifts and gift expenses, costs PPh section 21, the cost of the phone, other tax expenses, other operating expenses.